Factibilidad para la creación de un museo arqueológico para la conservación y uso del patrimonio cultural en el recinto Cuatro Manga, cantón san jacinto de Buena Fe año 2015 - Matute Oleas, Yolanda Johanna (2016)
This research project Feasibility Feasibility named for the creation of the Archaeological Museum in Precinct Four Tabara Mangas, San Jacinto canton of Buena Fe, 2015. The project has raised, according to the technical conditions and service requirements to bid. Starting point was the Situational Diagnosis whose purpose is to identify the need for the product, analyzing the supply and the demand for the purpose of establishing marketing strategies to spread tourists and residents of the sector; cultural heritage and which allows display the artifacts and paintings, considering that the main problem that there is no company that is dedicated to the exhibition, it is therefore very favorable start executing the project engaged in this activity. For the development of the study was necessary to use the methodology and types of research the historical and descriptive methods used for data collection were: empirical, deductive, analytical and statistical, that allowed us to analyze the data collected for the study market and demand analysis implemented through instruments such as the survey of 382 inhabitants there were 98% of support for the creation of the museum. The technical study (engineering project), size, location, infrastructure according to the type of needs, distribution areas and spaces required for the implementation of activities in which to undertake the project, as well as generation processes service costs and personnel requirements. The investment needed for the project specified in the financial study chapter detailed in the Financial Statements pro-forma projects, such as: Income Statement, Balance Sheet and Cash Flow, the latter serving as the basis for the corresponding financial assessment to determine the study economic and financial a Net Present Value (NPV) of $ 48.116,49 and an Internal rate of Return (IRR) of 37,42%, which has period payback of 1 year, 3 months and 7 days was obtained and a reasonable benefit cost $ 1.42. After the respective economic and financial studies was reached to determine the feasibility and economic and financial sustainability of the project. Keywords: Feasibility, creation, archaeological museum, cultural heritage